Influencia de la concentración de hidróxido de sodio y tiempo de lixiviación sobre el porcentaje de eliminación de arsénico presente en minerales auríferos refractarios usando lixiviación alcalina - Zamalloa Barrera, Jorge Guillermo (2017)
ABSTRACT In the present research work, the influence is evaluated of the sodium hydroxide concentration and the time of operation on the percentage (%) of the removal of arsenic present in a refractory auriferous concentrate from the northern region of Peru, using leaching Alkaline. To carry out of the test, the samples of concentrate of 200 g (20% solids) in a volume of 1 L. and with a grain size of -325 mesh (45um), at a temperature of 80°C, with addition of air and agitation, were subjected to different concentrations of sodium hydroxide 1.25 M, 1.5 M, and 1.75 M., and at different operating time levels of 1.5hrs. 2.5hrs. and 3.5hrs. to obtain the maximum percentage (%) of arsenic removal, using alkaline leaching. The mineralogical study of the sample of refractory gold concentrate concluded that despite having studied three polished sections to have a larger study area, no native gold grain or free gold minerals were observed, which reinforces the belief that gold occurs As a solid solution within arsenopyrite or pyrite or both (Annex B). The final results obtained show that at a concentration of 1.25M and with an operating time of 3.5 hrs., the maximum percentage (%) of arsenic removal of 59.78% was obtained, leaving the residue with a 2.18% arsenic law. From the above, and based on the statistical analysis carried out, it can be stated that the sodium hydroxide concentration and the operating time significantly influence the percentage (%) of arsenic removal from the refractory auriferous concentrate.